Edukasi “Tamba Resa” (Tanaman Herbal Keluarga dan Rempah Nusantara) pada Anak Usia Dini di Desa Pandian - Herowati; Lutfiana Fazad Azizah (IAIN Madura, 2021)
Plants that grow around students' homes and schools can be developed as learning media. It can be used as a learning tool for an early age to get to know Indonesia's natural wealth as our pride. They deserve to be educated so they can preserve and love Indonesia more. With the diversity of its natural resources through the PKM program with the title